cGMP Inhibits GTP Cyclohydrolase I Activity and Biosynthesis of Tetrahydrobiopterin in Human Umbilical Vein Endothelial Cells - Hiroaki Shiraishi; Taiya Kato; Koji Atsuta; Chiho Sumi-Ichinose; Masatsugu Ohtsuki; Mitsuyasu Itoh; Hitoshi Hishida; Shin Tada; Yasuhiro Udagawa; Toshiharu Nagatsu; Yasumichi Hagino; Hiroshi Ichinose; et al. (Elsevier, 2003)
ABSTRACT: Tetrahydrobiopterin (BH4) acts as an essential cofactor for the enzymatic activity of nitric oxide (NO) synthases. Biosynthesis of the cofactor BH4 starts from GTP and requires 3 enzymatic steps, which include GTP cyclohydrolase I (GCH I) catalysis of the first and rate-limiting step. In this study we examined the effects of cGMP on GCH I activity in human umbilical vein endothelial cells under inflammatory conditions. Exogenous application of the cGMP analogue 8-bromo-cGMP markedly inhibited GCH I activity in the short term, whereas an cAMP analogue had no effect on GCH I activity under the same condition. NO donors, NOR3 and sodium nitroprusside, elevated the intracellular cGMP level and reduced GCH I activity in the short term. This inhibition of GCH I activity was obliterated in the presence of an NO trapper carboxy-PTIO. NO donors had no effect on GCH I mRNA expression in the short term. Moreover, cycloheximide did not alter the inhibition by NO donors of GCH I activity. These findings suggest that stimulation of the cGMP signaling cascade down-regulates GCH I activity through post translational modification of the GCH I enzyme.